2016
DOI: 10.1007/s13361-016-1367-3
|View full text |Cite
|
Sign up to set email alerts
|

Ion Mobility Separation of Peptide Isotopomers

Abstract: Differential or field asymmetric waveform ion mobility spectrometry (FAIMS) operating at high electric fields fully resolves isotopic isomers for a peptide with labeled residues. The naturally present isotopes, alone and together with targeted labels, also cause spectral shifts that approximately add for multiple heavy atoms. Separation qualitatively depends on the gas composition. These findings may enable novel strategies in proteomic and metabolomic analyses using stable isotope labeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(98 citation statements)
references
References 33 publications
2
96
0
Order By: Relevance
“…The specification of isotopic envelopes was not considered in IMS until very recently (Valentine & Clemmer, ), as all isotopologues were previously indistinguishable because of limited resolution. With the improvements in resolving power of both linear IMS and FAIMS, separation of isotopologues is now possible (Shvartsburg, Clemmer, & Smith, ; Kaszycki, Bowman, & Shvartsburg, ; Kirk, Raddatz, & Zimmermann, ) and necessitates defining the isotopic composition of species in question. By analogy to MS, we propose in linear IMS the monoisotopic ion mobility (raw or reduced) for the monoisotopic species, average mobility for the integral over full mobility distribution for all natural isotopologues, and most probable mobility for the most abundant isotopologue.…”
Section: Reporting Ion Mobility Measurementsmentioning
confidence: 99%
“…The specification of isotopic envelopes was not considered in IMS until very recently (Valentine & Clemmer, ), as all isotopologues were previously indistinguishable because of limited resolution. With the improvements in resolving power of both linear IMS and FAIMS, separation of isotopologues is now possible (Shvartsburg, Clemmer, & Smith, ; Kaszycki, Bowman, & Shvartsburg, ; Kirk, Raddatz, & Zimmermann, ) and necessitates defining the isotopic composition of species in question. By analogy to MS, we propose in linear IMS the monoisotopic ion mobility (raw or reduced) for the monoisotopic species, average mobility for the integral over full mobility distribution for all natural isotopologues, and most probable mobility for the most abundant isotopologue.…”
Section: Reporting Ion Mobility Measurementsmentioning
confidence: 99%
“…Whereas the separation in DTIMS is based on an ion’s CCS-to-charge ratio, the separation in FAIMS results from the mobility difference of the analyte and buffer gas interactions in both strong and weak electric fields. FAIMS has been utilized for pharmaceutical analyses (119), separating charge states (120, 121), and recently, its power to distinguish isobars (122), isomers (123), isotopomers (124), and protein conformers (125) has been highlighted. Both DTIMS and FAIMS have shown great potential in enhancing biological analyses when coupled with MS platforms by reducing chemical noise and detecting low-abundance analytes in complex biological matrices (126).…”
Section: Field Asymmetric–and Drift Tube Ion Mobility Spectrometry–mamentioning
confidence: 99%
“…Previous studies have reported the benefits of FAIMS to improve proteome coverage and to reduce the extent of co-fragmentation that impedes the identification of low-abundance peptide ions (28)(29)(30)(31)(32)(33). The separation capability of FAIMS also facilitates the resolution of isomeric peptides, including histone variants and isomeric phosphopeptides (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Furthermore, the reduction of peptide co-elution and co-fragmentation observed with FAIMS can significantly improve the accuracy and the comprehensiveness of multiplex proteomic analyses (45).…”
Section: Introductionmentioning
confidence: 99%